Phenology and Foral Biology of Acer caesium Wall. - Semalty, R. K.; Sharma, C. M. (Indian Forester, 1996)
Phenology and floral biology of Acer caesium Wall. From the Kumaun Central Himalaya were studied in relation to leaf sprouting, flowering and anthesis, fruit setting, development and retention and leaf and fruit drop along with its floral biology in relation to pollen germination and viability in-vitro. The emergence of new leaves starts in the last week of February along with the floral buds. The maximum anthcsis occurs between 12 noon to 2 p.m. (upto 40%) at a temperature between 4.5Â°C to 20.5Â°C and RH, 87% to 88.5%. The total period of flowering for the species was 48 days. The average fruit setting percentage in Acer caesium had been recorded as 88.84% in the year 1994 after 20 days of pollination, whereas it remains only 75.96% after 50 days of pollination. The leaf drop and fruit drop starts in the month of October and the natural regeneration by the seeds takes place in the next monsoons. The highest percentage of pollen germination (71.55% in 10% sucrose and 69.38% in 150 ppm of GA3 after 48 hrs of its culture) and viability (75.36%) reflacts the reproductive capacity and number of pollen grains required (or controlled pollination studies in Acer caesium for undertaking any breeding programme.